2023
DOI: 10.1080/20008066.2022.2163129
|View full text |Cite
|
Sign up to set email alerts
|

Associations between coping strategies and psychological distress among people living in Ukraine, Poland, and Taiwan during the initial stage of the 2022 War in Ukraine

Abstract: Background: The 2022 War in Ukraine has significantly affected the psychological well-being and daily lives of people in many countries. Objective: Two aims of this transnational study were (1) to compare psychological distress and coping strategies among people living in Ukraine, Poland, and Taiwan, (2) to examine whether the associations between various coping strategies (ie. problem-focused coping, emotion-focused coping, and avoidance) and psychological distress (ie. depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 40 publications
7
23
0
Order By: Relevance
“…Among the Ukrainian participants, the Cronbach's alpha values of DASS‐21 for the depression, anxiety, and stress subscales were 0.8, 0.85, and 0.84, respectively. Among the Polish participants, the Cronbach's alpha values of DASS‐21 for the depression, anxiety, and stress subscales were 0.88, 0.86, and 0.88, respectively 13 …”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Among the Ukrainian participants, the Cronbach's alpha values of DASS‐21 for the depression, anxiety, and stress subscales were 0.8, 0.85, and 0.84, respectively. Among the Polish participants, the Cronbach's alpha values of DASS‐21 for the depression, anxiety, and stress subscales were 0.88, 0.86, and 0.88, respectively 13 …”
Section: Methodsmentioning
confidence: 96%
“…The current study derived data from a cross‐sectional online survey conducted from March 8 to April 26, 2022, in Poland, Ukraine, and Taiwan 13 . The participants who completed the survey were from the general population living in Ukraine, Poland, and Taiwan during the initial stage of the Russo‐Ukrainian War.…”
Section: Methodsmentioning
confidence: 99%
“…It is concluded that students deal with stress by avoiding it or facing it, but almost always alone. However, seeking professional help can be crucial in the adjustment process (Chudzicka-Czupała et al, 2023 ). If counseling services were promoted and shown to be effective, more students might consider benefiting from them instead of relying on maladaptive coping strategies that can lead to experiencing depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature has examined coping strategies and their association with various outcomes among international students. For example, one study found that international students who used emotion-focused coping strategies (such as seeking social support or using positive reframing) reported higher levels of psychological wellbeing and lower levels of stress (Chudzicka-Czupała et al, 2023 ). Another recent study examined mindfulness as a coping strategy for international students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Data of this study were collected through a cross-sectional online survey conducted from March 8 to April 26, 2022 in Poland, Ukraine, and Taiwan. 18 We recruited participants from the general population residing in Poland, Ukraine, and Taiwan during the initial stage of the Russo-Ukrainian War. However, we only included data from Poland and Ukraine in the current study because that we investigated the impact of rumination for Russo-Ukrainian War.…”
Section: Methodsmentioning
confidence: 99%